Communication Patterns of Silverbird Taxi Drivers in Providing Services to Passengers - Callysta, Ghavira Desfi; Mirawati, Ira; Nurfadila, Frila (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2025)
This study analyzes the communication patterns of Silverbird drivers in providing services to passengers, focusing on the application of the 5S Standard (Salam, Sapa, Senyum, Sopan, Selamat) and reward and punishment-based performance evaluation. Using a qualitative approach and case study method, data was collected through interviews, observations, and literature review of drivers in the Ciputat Pool. The results showed that communication is structured in three stages: pre-trip (route confirmation and luggage assistance), on-trip (passenger-initiated interaction), and post-trip (contact exchange for loyalty). The 5S standard is key in ensuring ethical communication, while rigorous evaluation covers four aspects: service, accidents, working days, and tenure bonus. Critical findings highlighted that 70% of passenger complaints were related to SOP violations, especially fleet cleanliness and driver appearance. Reward systems such as “Dedicated Car” cars for high-performing drivers and punishment (relegation to Bluebird Taxi) are effective in maintaining a premium image. Key barriers include language differences (particularly Mandarin) and passive feedback from passengers. The research recommends the development of intercultural communication training, integration of real-time feedback through the MyBluebird app, and transparency in coach evaluation. Academic implications emphasize the need for further studies on the impact of nonverbal communication (fleet cleanliness, appearance) on customer loyalty and perception of foreign passengers.